2008
DOI: 10.1007/bf03342704
|View full text |Cite
|
Sign up to set email alerts
|

Price Delegation in Sales Organizations: An Empirical Investigation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…So far, however, empirical research on price delegation is very limited in the sales management literature. Indeed, to our knowledge, the only published empirical study following the early work of Stephenson et al (1979) is that of Hansen, Joseph, and Krafft (2008). Further, the extant empirical studies have limitations.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…So far, however, empirical research on price delegation is very limited in the sales management literature. Indeed, to our knowledge, the only published empirical study following the early work of Stephenson et al (1979) is that of Hansen, Joseph, and Krafft (2008). Further, the extant empirical studies have limitations.…”
Section: Introductionmentioning
confidence: 79%
“…Specifically, Stephenson, Cron, and Frazier (1979) report that only 23% of all responding firms in their survey gave full pricing authority, while 48% gave medium authority (i.e., pricing latitude was limited to pre-specified ranges), and 29% granted low pricing authority to their sales forces (i.e., sales personnel had no authority to deviate from list prices or could do so only with prior management approval). More recently, a survey by Hansen, Joseph, and Krafft (2008) found that only 11% of all firms fully delegate pricing decisions, while 28% of the responding companies yield no pricing authority at all to their sales forces (i.e., price is determined exclusively by management).…”
Section: Introductionmentioning
confidence: 98%
“…According to Stephenson et al (1979), in the hospital supplies industry, only 23% of firms give full pricing authority to salespeople; others allow no (29%) or limited (48%) authority. Hansen, Joseph, and Krafft (2008) report that among their sample of 222 German sales organizations from various industries, only 11% grant their sales reps full pricing authority, whereas 28% give none and 61% allow only limited pricing authority. Our findings should prompt firms that limit pricing authority to think carefully about the indirect ways in which they might guide sales reps' behavior by using insights from behavioral economics, applied to the context of price negotiations.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, Stephenson, Cron, and Frazier (1979) report that only 23% of all responding firms in their survey gave full pricing authority, while 48% gave medium authority (i.e., pricing latitude was limited to pre-specified ranges), and 29% granted low pricing authority to their sales forces (i.e., sales personnel had no authority to deviate from list prices or could do so only with prior management approval). More recently, a survey by Hansen, Joseph, and Krafft (2008) found that only 11% of all firms fully delegate pricing decisions, while 28% of the responding companies yield no pricing authority at all to their sales forces (i.e., price is determined exclusively by management).…”
mentioning
confidence: 99%
“…So far, however, empirical research on price delegation is very limited in the sales management literature. Indeed, to our knowledge, the only published empirical study following the early work of Stephenson et al (1979) is that of Hansen, Joseph, and Krafft (2008). Further, the extant empirical studies have limitations.…”
mentioning
confidence: 99%